Dicrostonyx vinogradovi Ognev 1948 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Dicrostonyx vinogradovi Ognev, 1948. Mammals of Eastern Europe and Northern Asia, 6:509. TYPE LOCALITY: U.S. S. R., Wrangel Isl. DISTRIBUTION: Known only from the type locality. COMMENT: Formerly included in torquatus; karyological and morphological analyses, and experimental breeding indicated species distinction; see Chernyavskii and Kozlovskii, 1980, Zool. Zh., 59(2):266-273. The diploid number is 28 and the fundamental number is 54. See also Rausch, 1977, in Sokolov, ed., [Adv. Mod. Theriol.], Acad. Sci. U.S. S. R., Nauka, Moscow, pp. 162- 177. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 484, DOI: 10.5281/zenodo.7353034